Molecular identification of yeasts from Turkish traditional cheeses: Extracellular enzyme activities and physiological properties important for dairy industry - MELİH GÜNAY; TÜLAY TURGUR GENÇ (Nusantara Bioscience, 2023)
Abstract. Gunay M, Genc TT. 2023. Molecular identification of yeasts from Turkish traditional cheeses: Extracellular enzyme activities and physiological properties important for dairy industry. Nusantara Bioscience 15: 1-11. The determination of yeast microbiota in cheeses and the physiological properties of yeasts are very important for the dairy industry. In addition, the physiological features, proteolytic and lipolytic activities, and stress tolerance of yeasts have a significant role in the selection of starter yeast species for cheese ripening. This study aimed to determine industrially important yeasts isolated from cheese samples. Molecular techniques identified the isolated yeast strains. The yeast strains’ extracellular enzyme activities, fermentation capacities, and thermotolerance and osmotolerance properties were also evaluated. A total of 81 yeast strains were isolated and characterized from three types of cheese samples. PCR-RFLP determined the isolated yeast strains and sequence analysis of ITS1-5.8S-ITS2 and 26S rDNA regions. A maximum parsimony tree was constructed by MEGA X software to evaluate the phylogenetic relationship of identified yeast strains. Candida intermedia, Candida parapsilosis, Clavispora lusitaniae, Debaryomyces hansenii, Kluyveromyces marxianus, Pichia kudriavzevii, and Wickerhamomyces anomalus yeast species were identified on cheese samples. The distribution of identified yeast species on cheese samples was determined as 48.1% for W. anomalus, 17.3% for K. marxianus, 14.8% for C. parapsilosis, 8.6% for D. hansenii, 4.9% for Cl. lusitaniae, 3.7% for C. intermedia and 2.5% for P. kudriavzevii. The W. anomalus yeast species was common in three cheese types. All strains of W. anomalus and P. kudriavzevii yeast species, three C. parapsilosis, and two Cl. lusitaniae yeast strains have important physiological properties for industrial applications. These yeast strains have the potential to be used in combination as starter cultures to improve cheese maturation in the future. This comprehensive study identifies yeast species by ITS1-5.8S-ITS2 and 26S rDNA regions and determines industrially important yeast species using multiple criteria (extracellular enzyme activity, stress tolerance, and fermentation capacity).